COVID-19 aus Sicht der Pneumologie – Langzeitfolgen und Implikationen für die pneumologische Nachsorge - Leo, Fabian; Wormanns, Dag; Grohé, Christian (DMW - Deutsche Medizinische Wochenschrift, 2020)
The long-term sequelae of COVID-19 on are not yet predictable. Radiological and histopathological data on COVID-19 and observational studies after the SARS-CoV-1 pandemic 2003/2004 suggest that in a proportion of COVID-19 patients, functional limitations due to pulmonary fibrosis and other patterns of lung damage may persist. Systematic follow-up, based on prudent pulmonary function testing, is warranted for the correct diagnosis, graduation and treatment of the underlying pathology at an early stage. This review summarizes the potential spectrum of Post-COVID-19 pulmonary disease patterns and provides recommendations for the follow-up care of COVID-19 patients in the field of respiratory medicine.
Keywords: Langzeitfolgen; Lungenfibrose; radiologische Befunde; systematisches Follow-up; diffuser Alveolarschaden